11 A medical device-grade T2 phantom for quality assurance of inflammation imaging by CMR. (1st November 2021) - Fornasiero, Massimiliano; Pierce, Iain; Webber, Matthew; Keenan, Kathryn E; Stupic, Karl F; Bruehl, Rüdiger; Ittermann, Bernd; Pang, Wenjie; Hughes, Alun D; Nezafat, Reza; Kellman, Peter; Moon, James C; et al.
Abstract : Introduction: Cardiovascular magnetic resonance (CMR) T2 mapping is key to quantifying myocardial inflammation. Use of T2 mapping in clinical studies is burgeoning but in the absence of a quality control system, single-center findings are not generalizable and longitudinal studies cannot reliably track alterations in T2 times reflecting the inflammatory state of the myocardium. Aim: We used our expertise gained from the development of the T1 Mapping and Extracellular Volume (T1MES) phantom, to develop a dedicated T2 mapping CMR phantom to medical device standards. Method: A design collaboration including a specialist MRI small-medium enterprise, clinicians, physicists and national metrology institutes was formed. A T2 mapping phantom ( figure 1 i ) was designed to cover clinically relevant T1 and T2 times in native and post-contrast myocardium across field-strengths ( figure 1 iii, v ). Two earlier prototypes had been manufactured and tested, with the third and final one being reported here. Results: The T2 mapping phantom which can be used at both 1.5 and 3 Tesla is an agarose gel-based phantom using nickel chloride as the paramagnetic relaxation modifier. It contains nine differently-doped agarose gel tubes embedded in a gel/beads matrix. The phantom was free of air bubbles and susceptibility artifacts at both field strengths ( figure 1 ii ) and T2 maps were free from off-resonance artifacts ( figure 1 iv ). The incorporation of high-density polyethylene beads in the main gel fill was effective at flattening the B 0 and B 1 fields ( figure 2 i, ii ). T1 and T2 times measured in the phantom showed coefficients of variation of ≤1% between repeat scans indicating good short-term reproducibility. Temperature dependency experiments conducted at the national metrology institutes ( figure 2 iii ) confirmed that over the range 13–40°C the short-T1/2 tubes were more stable with temperature than the long-T1/2 tubes. Conclusion: The program has developed a T2 mapping phantom for CMR replicating clinically relevant T1/T2 times across myocardial health and disease. The device will be shortly listed under the Food and Drug Administration (FDA) database and Conformité Européene (CE) marking. Reproducible mass manufacture of this phantom may now commence to support the use of T2 mapping in longitudinal cohort studies, multicentre research or inflammation imaging.